Hidden treasure in an endoscopically retrieved oesophageal trichobezoar. (18th January 2013) - Renji, Elizabeth; Nathan, Anand K; Dalzell, Mark A
Abstract : A 12-year-old girl with Smith-Lemli-Opitz syndrome and gastrostomy dependency presented with multiple episodes of coffee ground vomits. An upper gastrointestinal endoscopy revealed a trichobezoar in the lower oesophagus, with a 'hidden treasure'—a retained end of a G tube at the core. Endoscopic retrieval led to resolution of symptoms. Literature is scant with only one previous report of an oesophageal trichobezoar. Techniques of removal of percutaneous endoscopic gastrostomy in children are reviewed. The pathogenesis, preventative measures and management for oesophageal trichobezoars are discussed.